Child wonder a novel - Jacobsen, Roy 1954- (Lannan translation series selection., 2011)
"Nine-year-old Finn and his mother find comfort in each other's company as they struggle to get by in a working-class suburb of Oslo. But when a half sister Finn never knew joins the household, their familiar routines are upset. Finn takes the girl under his wing over an idyllic summer on an island in Oslofjord, but he can't understand why everyone thinks his new sister is so different from other children. Nor can he fathom his mother's painful secret, one that pushes them even futher apart. As summer comes to a close, Finn must attempt to grasp the incomprehensible adult world and his place within it."--P. [4] of cover.